Features, labels, space, and time: factors supporting taxonomic relationships in the anterior temporal lobe and thematic relationships in the angular gyrus. Issue 10 (26th November 2019) - Davis, Charles P.; Yee, Eiling
ABSTRACT: Having the concept coffee involves knowing not only how coffee looks, smells, and tastes, but also how it relates to other things. We consider two types of conceptual relationships: (1) taxonomic, i.e. between entities that share multiple features (e.g. coffee–tea), and (2) thematic, i.e. what things "go together" in an event (e.g. coffee–spoon). We first review data suggesting that taxonomic and thematic relations are supported by semantic "hubs" in the anterior temporal lobe (ATL) and angular gyrus (AG), respectively. We then propose that the AG's connectivity to hippocampal regions supports its sensitivity to episodic detail and hence the event structures and context-sensitivities characterizing thematic relations, and that ATL's connectivity with perirhinal cortex, which supports discrimination, promotes taxonomic categorization. Finally, we discuss several reasons that labelling may be particularly critical for taxonomic relations, and propose that processing in ATL is influenced by labels because of connectivity with frontal language regions.